In vivo potential of polymeric N-acryloyl-glycine nanoparticles with anti-inflammatory activities for wound healing - Gupta, Prem Shankar; Wasnik, Kirti; Singh, Gurmeet; Patra, Sukanya; Pareek, Divya; Yadav, Desh Deepak; Tomar, Munendra Singh; Maiti, Somedutta; Singh, Monika; Paik, Pradip (Royal Society of Chemistry, 2023)
An optimal wound-healing process requires highly coordinated and regulated interactions between the immune and biological systems since long-term wounds are severe clinical issues which make patients vulnerable to potentially fatal microbial infections. Therefore, it is essential to develop new treatments and therapeutic strategies. We aimed to develop a poly(N-acryloyl glycine) nanoparticle (PNAG NP) based formulation, which is effective to accelerate skin restoration. PNAG NPs ca. 35 nm in size (in dia.) have been synthesised through the mini-emulsion radical polymerisation technique and formulated with an ointment base for the establishment of wound healing application. Biocompatible, hemocompatible, proliferative and migration enhancer PNAG NPs were formulated as a PNAG nanoformulation, which showed a ∼31% higher wound healing efficiency compared to the control group of samples in the in vivo assessment. Periodic evaluation of TNF-α and IL6 for the treatment group shows the change in their levels from 4.10 ± 3.18 to 5.17 ± 3.27 pg mL−1 and 11.93 ± 2.34 pg mL−1 to 10.33 ± 3.31 pg mL−1, respectively, consistent with the reduction in inflammation. The increased level of IGF-1 from 25.41 ± 13.56 ng mL−1 to 64.22 ± 16.93 ng mL−1 in the PNAG test group could be correlated with the increase in angiogenesis followed by an increase in the wound healing efficiency. This study showed that PNAG NPs could execute rapid coordination between cell proliferation and migration, anti-inflammatory actions, and simultaneous regeneration of skin tissues without the use of any of the external synergistic factors like drugs, genes or cells. Thus, the intriguing results showed that the PNAG NPs could address the existing wound healing challenges and can serve as a potential material for regenerative purposes.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: N-acryloyl glycine; PNAG NPs; hemocompatible; Biocompatible; nanoformulation